Highly Selective Current‐Induced Accumulation of Trace Ions at Micro‐/NanoPorous Interfaces. Issue 6 (3rd April 2019) - Bondarenko, Mykola P.; Bruening, Merlin L.; Yaroshchuk, Andriy
Abstract: During application of electrical current through composite micro‐/nanoporous membranes, trace‐ion accumulation in the microporous layer should vary greatly with the ion diffusion coefficient to allow selective accumulation of specific ions. This study examines the theoretical enrichment factors in the microporous region as a function of current density and trace‐ion diffusion coefficient. Trace‐ion accumulation relies on charged nanopores that exclude coions, which gives rise to depletion of the dominant salt and high local electric fields in the region next to the nanopores. Trace ions accumulate in this region because convection carries them toward the nanoporous interface, whereas electromigration in the opposite direction is strongest next to the interface. With monovalent coions having 2% difference in diffusion coefficients, calculated accumulation selectivity factors reach >1.2. Such selectivities may prove useful in separating very similar species such as isotopes or equally charged peptides. Abstract : In current‐polarized composite micro‐/nanoporous membranes, dominant‐salt concentration can go down considerably close to the micro‐/nano‐interface, which causes strong increases in the local electric field. Trace coions can accumulate in the microporous region because convection carries them toward the interface, whereas opposite electromigration gets strongest next to it. This accumulation can be highly selective wrt the trace‐ion diffusion coefficient.